Mediating Market Moralities: Making Personalized Apps in the 'Attention Economy'. - Otto, Eva Iris (Social Analysis, 2024)
This article considers how actors within digital markets creatively navigate moral ambiguities in their work, and how this shapes the building of (software) material relations. Catching the attention of an app user is considered morally ambiguous behavior in the 'attention economy' discourse shaping the Danish app market. Employees of the Danish app agency Monocle navigate this moral ambiguity by 'personalizing' apps so that they become relevant at the 'right time'. However, in app-building practices, this entails a set of quite different personalized configurations. Consequently, I argue that personalization works to mediate different values within digital markets. It thereby allows app makers to pursue projects of fashioning themselves as makers of apps that are 'good', both in a technical and moral sense, while making apps that also 'win the market'.